2011
DOI: 10.4103/2231-0746.92785
|View full text |Cite
|
Sign up to set email alerts
|

Vocal cord paralysis following orthognathic surgery intubation

Abstract: The incidence of recurrent laryngeal nerve paralysis following short-term oro-endotracheal intubation for any surgical procedure is very rare. The diagnosis becomes very difficult if the surgical procedure may alter the vocal characteristics following surgery. We report a case of a 24 year-old healthy male patient who developed prolonged hoarseness which developed after having undergone a bimaxillary orthognathic surgical procedure. Following surgery, the patient's complaints of hoarseness and mild coughing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Incorrect endotracheal placement of the tracheal tube can lead to serious complications, such as laryngeal nerve paralysis and accidental extubation [4]. To ensure that the cuff passes below the glottis, the Parker tube has a marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorrect endotracheal placement of the tracheal tube can lead to serious complications, such as laryngeal nerve paralysis and accidental extubation [4]. To ensure that the cuff passes below the glottis, the Parker tube has a marker.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to determine accurately the positioning of the tracheal tube. Additionally, recurrent laryngeal nerve paralysis caused by the cuff of the tracheal tube has been reported [4]. Therefore, the position of the cuff should be such as to avoid excessive pressure on the cricoid cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of VCP is very low [6]. Fauzdar et al [7] reported the only case of VCP after an orthognathic surgery. The change in the voice quality of the cases is thought to be caused by injury to the recurrent laryngeal nerve during EI.…”
Section: Discussionmentioning
confidence: 99%
“…Incorrect endotracheal placement of the tracheal tube can lead to serious complications, such as laryngeal nerve paralysis and accidental extubation [1]. In oral and maxillofacial surgery and dental procedure, the head of the patient was covered in drape, and an anesthesiologist cannot often see tracheal tube.…”
Section: Introductionmentioning
confidence: 99%